Gut microbiota and autism spectrum disorder: advances in dietary intervention strategies based on the microbiota-gut-brain axis mechanism - Ziji Fang; Yinxiong Zhou; Ke Chen; Juelan Wang; Xiaoli Liu; Ping Jia (Frontiers in Neuroscience)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder that is primarily characterized by deficits in social interaction, impaired communication, restricted interests, and repetitive behaviors. The prevalence of ASD has been steadily increasing, establishing it as one of the leading causes of disability among children worldwide. Although the precise pathogenesis of ASD remains unclear, factors such as genetic predisposition, environmental exposures, immune dysregulation, and neurodevelopmental abnormalities are collectively believed to contribute to its onset. In recent years, the gut microbiota has emerged as a promising area of research in neurobiology, particularly in relation to advances in understanding the microbiota–gut–brain axis (MGBA) mechanism. Studies have shown that children with ASD exhibit significant dysbiosis in their gut microbiota, which may affect brain function via the MGBA, ultimately leading to abnormal behaviors and impaired emotional regulation. This review summarizes the role of the gut microbiota in the pathogenesis of ASD, examining how alterations in gut permeability, dysregulated microbial metabolites, and immune dysfunction may influence ASD symptomatology. In particular, the role of the MGBA in modulating immune-inflammatory responses, neurodevelopment, and behavioral regulation has become a focal point of ASD research. Building on this foundation, the review further summarizes dietary intervention strategies grounded in the MGBA theory, emphasizing their potential to restore gut microbial composition, modulate immune responses, and enhance metabolic function, thereby offering novel therapeutic perspectives for ASD.